A theory of loosening earth pressure above a shallow tunnel in unsaturated ground. (26th March 2020) - Fang, Xu; Kikumoto, Mamoru; Cui, Ying
Summary: A theory is proposed to evaluate the loosening earth pressure (vertical earth pressure after excavation) acting on a shallow tunnel in unsaturated ground with an arbitrary groundwater level. The theory is developed based on the limit equilibrium theory, combining soil–water characteristic curves, Mohr–Coulomb failure criteria, and effective stress for unsaturated soils. The proposed theory is applied to predict the vertical distribution of loosening earth pressure in unsaturated ground, which shows a significant difference from that in saturated ground. In unsaturated ground, suction contributes to the increase in effective loosening earth pressure and shear resistance. The remarkable effects of groundwater depth, soil type, and scale of overburden height and trapdoor width on loosening earth pressure are also revealed. Based on the soil–water characteristic curve, the degree of saturation decreases, which causes wet density to decrease and the total and effective loosening earth pressures to have contrary tendencies. Moreover, effective loosening earth pressures vary with soil type as the degree of saturation varies. The total loosening earth pressures are, however, very similar regardless of soil type, because wet density and shear resistance have similar tendencies. The proposed theory provides a valid model for loosening earth pressure in unsaturated ground that will be useful for shallow tunnel excavations.